249 Evaluation of FluidQuip Dried Distillers Grains plus Solubles in Cattle Finishing Diets - Wiseman, Aksel (J Anim Sci, 2020)
A 112 d finishing study was conducted to evaluate the effects of feeding dried distillers grains plus solubles (DDGS) from the MSC-Fiber stream of the FluidQuip post-fermentation fiber separation process compared to conventional DDGS. Yearling crossbred steers (n = 240, initial BW = 463 ± 35kg) were blocked by initial BW, stratified by BW, and assigned randomly to pen (n = 30; 8 steers/pen). Treatments were arranged as a 2×2 + 1 factorial with DDGS type (MSC DDGS [MSC]; Conventional DDGS [CONV]) and inclusion level (20 or 40% diet DM) as the factors. All treatments were compared to a corn-based control (CON). DDGS replaced a 60:40 blend of high-moisture corn and dry-rolled corn. All diets contained 7.5% alfalfa hay and supplement. Data were analyzed as a randomized block design with pen as experimental unit and block as fixed effect. Increasing concentrations of CONV or MSC resulted in a linear increase in DMI (P < 0.01). Steers fed 40% MSC had the greatest DMI (P < 0.01) while CON steers had the least (P < 0.02). Daily gains for MSC steers linearly increased (P = 0.03), while CONV steers showed a tendency for a quadratic response to ADG (P=0.08). Feed efficiency of CONV steers increased quadratically (P = 0.04) and tended to decrease linearly (P = 0.09) for steers fed MSC. Efficiency was greatest for 20% CONV but not different (P > 0.16) than CON, or 20% MSC. Steers fed 40% MSC or 40% CONV were not different in feed efficiency. Inclusion of MSC DDGS resulted in linear increases in DMI and ADG over CON, but decreased feed efficiency by 1.0 and 5.3% resulting in MSC DDGS having a relative feeding value of 95.0 and 86.7% of corn at 20 and 40% DM, respectively.